Amplification and Over-Expression of the MDM2 Gene in Human Soft Tissue Tumours. (1997) - Patterson, Helen; Barnes, Diana; Gill, Sandra; Spicer, James; Fisher, Cyril; Thomas, Merion; Grimer, Robert; Fletcher, Chris; Gusterson, Barry; Cooper, Colin
Abstract : Purpose . Amplification of genetic sequences on chromosome 12q13 is frequently found in soft tissue tumours. However, for the MDM2 gene, over-expression of the MDM2 protein has not always been shown to accompany gene amplification, raising the possibility that amplification of genetic sequences targets alternative genes on chromosome 12q13 for over-expression. To investigate this discrepancy, we have examined 129 soft tissue tumours for amplification of the MDM2 gene using Southern analysis, and 39 of these tumours were also examined by immunohistochemical staining for MDM2 over-expression. Results . Gene amplification was identified in 14/114 (12.3%) of the malignant tumours, but was not identified in any of the benign tumours; 21/39 (54%) of the malignant tumours also demonstrated MDM2 over-expression. Within this group the MDM2 gene was over-expressed in every tumour in which the gene amplification was found, and over-expression in the absence of gene amplification was also found in an additional 10 tumours. Discussion . These data demonstrate a clear correlation between the presence of MDM2 amplification and MDM2 over-expression, and provide persuasive evidence therefore that the amplification of genetic sequences on chromosome 12q13 in soft tissue sarcomas targets the MDM2 gene for over-expression. These data also indicate that alternative mechanisms may contribute to MDM2 over-expression within some tumours.